Analysis Of Audit Procedures On Receivables at BHK Foundation By KAP Djoko Soerjadi - Mochammad David Hardiansyah; Sri Trisnaningsih (International Journal Business, Management and Innovation Review, 2025)
Accounts receivable are one of the most liquid and crucial assets for businesses, impacting their long-term survival. Therefore, the examination and testing of these accounts receivable balances are mandatory for every public accounting firm. The objective of this research is to determine the accounts receivable audit procedures implemented by KAP Djoko Soerjadi and to evaluate these procedures. This research employs a qualitative approach with a descriptive analysis method, which involves collecting, classifying, organizing, presenting, and analyzing data obtained by the author from the BHK Foundation. The results of this research can be concluded that the accounts receivable audit process carried out by KAP Djoko Soerjadi is in accordance with applicable audit theories and standards, starting from accounts receivable audit planning, accounts receivable audit execution, reporting and concluding the results of the accounts receivable audit, and finally archiving. Despite the constraints related to data submission delays, KAP Djoko Soerjadi maintains communication and maintains good relationships while assisting the client.